Comparison on Hepatotoxicity Profile of Diclofenac Sodium & Diclofenac Potassium on Rabbits (Medical Forum Monthly, 2024)
Objective: Aim of this study was to determine the clinical hepatotoxicity of diclofenac sodium and of diclofenac potassium, further to evaluate whether these drugs could elicit liver cell destruction and anemia, and which drug is comparatively safer for prolong use.Study Design: Experimental study.Place and Duration of Study: This study was conducted in the Department of Pharmacology; Faculty of Pharmacy, University of Karachi, Duration of study was 30 days.Materials and Methods: Male 50 rabbits were equally divided into 5 groups, group A was served as control and the group B & C were diclofenac sodium(0.8mg/kg/day and 1.5mg/kg/day), and group D & E were of diclofenac potaasium (0.8mg/kg/day and 1.5mg/kg/day), treated. All the animals were caged in pair in an iron caged with free access to grass and hay of standard diet and tap water for a period of 30 days. At the end of 30 days blood was collected through cardiac puncture from each rabbit and was analyzed to determine the levels of SGOT, SGPT, Bilirubin, ESR and Erythrocyte count.Results: The experimental results suggest that SGOT and SGPT levels were significantly increased in diclofenac sodium treated rabbits after 10 and 30 days (P < 0.01), while diclofenac potassium treated rabbits showed significant result, (P < 0.05) only after 30 days of treatment.The level of bilirubin was significantly increased in diclofenac sodium treated rabbits after 10 days and 30 days (P < 0.01) and diclofenac potassium also showed significant result (P < 0.05) after 30 days treatment. Erythrocyte count decreased in both control and treated rabbits after 10 days but control results are not significant. After 30 days diclofenac sodium showed highly significant decreased count of erythrocytes (P < 0.01) but diclofenac potassium showed only significant results (P < 0.05). E.S.R values significantly increased in diclofenac sodium and diclofenac potassium treated rabbits after 10 days and 30 days.Conclusion: Our study concluded that as compared to sodium, potassium salt of diclofenac is safer for prolong pain management as the incidence of adverse effects were comparably lower in potassium salt..